2011
DOI: 10.1302/0301-620x.93b12.26989
|View full text |Cite
|
Sign up to set email alerts
|

Tranexamic acid in total knee replacement

Abstract: We conducted a systematic review and meta-analysis of randomised controlled trials evaluating the effect of tranexamic acid (TXA) upon blood loss and transfusion in primary total knee replacement. The review used the generic evaluation tool designed by the Cochrane Bone, Joint and Muscle Trauma Group. A total of 19 trials were eligible: 18 used intravenous administration, one also evaluated oral dosing and one trial evaluated topical use. TXA led to a significant reduction in the proportion of patients requiri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
122
2
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 338 publications
(135 citation statements)
references
References 31 publications
7
122
2
4
Order By: Relevance
“…However, the small surgical field and the increasing operative difficulty limit the popularity theses two approach [7], [8]. As a compromise of these approaches, mini-midvastus approach was introduced as it minimized the vascular and muscular disruption of knee and provided a relatively better operative exposure [6], [9]. Therefore, mini-midvastus approach has probably been the most popular approach in MIS TKA [10].…”
Section: Introductionmentioning
confidence: 99%
“…However, the small surgical field and the increasing operative difficulty limit the popularity theses two approach [7], [8]. As a compromise of these approaches, mini-midvastus approach was introduced as it minimized the vascular and muscular disruption of knee and provided a relatively better operative exposure [6], [9]. Therefore, mini-midvastus approach has probably been the most popular approach in MIS TKA [10].…”
Section: Introductionmentioning
confidence: 99%
“…14 Alshryda S et all found that the evidence from trials does not support an increased risk of deepvein thrombosis or pulmonary embolism due to TXA administration. 16 Ishida et all did similar study but the significant findings beyond the reduction in blood loss after knee arthroplasty is the reduction in knee swelling,which are often the chief complaint in follow up of patients after knee arthroplasty. Sa-ngasoongsong P et all did another strategy, they beside the use of tranexamic acid also did clamping of drain and found more favourable results as compared to using tranexamic acid alone or clamping of drain without using this drug.…”
Section: Discussionmentioning
confidence: 86%
“…Moreover, its efficacy and safety profile in orthopedic surgery is further supported by two meta-analyses of TXA use in primary hip [58] and knee [59] arthoplasty. In hip surgery, Sukeik et al [58] found that TXA reduced intraoperative blood loss by 104 mL and postoperative blood loss by 172 mL (n = 350).…”
Section: Orthopedic Surgerymentioning
confidence: 94%
“…There was also a proportional reduction of patients requiring blood transfusion (risk difference −0.20). In total knee replacement, Alshryda et al [59] found significant reduction in blood loss by 591 mL (n = 763). It should be noted that there was significant heterogeneity in the trials.…”
Section: Orthopedic Surgerymentioning
confidence: 99%
See 1 more Smart Citation